Applying Human Factors in Post Ambulatory Anesthesia Follow-Up Redesign - Liao, Alan H.W.; Lai, Ka-Man; Tsai, Hsi-Yi (Proceedings of the International Symposium of Human Factors and Ergonomics in Healthcare, 2025)
Post-anesthetic follow up includes non-clinical measures aimed at identifying relevant anesthesia-related complications, among other concerns. The conventional follow-up process for ambulatory patients uses intermediate communication channels, resulting in inconsistent contact success rates and varying work times. Combined with nursing shortages, this has led to decreased follow-up quality and staffing challenges, prompting a need to redesign the workflow and communication tools for improved task management. At Taipei Medical University Hospital, automated text messaging linked to a standardized web-based survey was introduced for all patients receiving ambulatory anesthetic services. This initiative achieved a satisfactory contact success rate and improved the overall follow-up coverage for ambulatory cases in the health-screening center. Additionally, it resulted in a weekly saving of thirty-six nursing hours, contributing to greater flexibility in nurse duty roster scheduling. The early results of this redesign initiative for post-ambulatory anesthetic follow-ups have been encouraging.